Князі Глинські: походження роду, Глинське князівство, володіння в Сіверській землі - Келембет, С. (Сiверянський лiтопис, 2019)
У статті розглядається питання про походження князів Глинських та їхні володіння на межі XIV – XV ст. Можна вважати встановленим, що вони були нащадками
знаменитого еміра (беклярібека) Мамая, який, у свою чергу, належав до монгольського
роду князів Киятів – найближчих родичів правлячої династії Чингізідів. Глинске князівство займало величезну, але малонаселену територію в басейні середньої і нижньої
течії р. Ворскли, Псла і Сули. Близько 1400 р. великий князь Вітовт надав Глинським
деякі володіння на Сіверщині, центром яких було містечко Хоробор на місці сучасного
смт Макошине Чернігівської обл. До числа перших Глинських або їхніх найближчих
родичів, скоріше за все, належав і князь Урустай Менський, згаданий у 1408 р. The article is devoted to the early history of the family of princes Hlynsky, as well as the
composition of their possessions in the late XIV – early XV centuries. In particular, the following
issues are being investigated: 1) the origin of the Hlynsky; 2) the territory of the Hlynsky
principality and its main centers; 3) Hlynsky possessions in Siver land, received by them from
Grand Duke Vitovt. In the existing historiography, these questions are clearly not studied.
Hlynsky were one of the few princely families of the Grand Duchy of Lithuania, who
had a Tatar origin. According to the «Genuine Genealogy of the Glinsky Princes», compiled in
Moscow in the first half of the 1520s, they were descended from famous Mamai, the de facto
ruler of the western part of Ulus Juchi in the 1360–1370s. Mamai belonged to the Mongol
tribe of princes Kyiatov, who were the closest relatives of the ruling dynasty of Chingizids.
Information «genuine genealogy» should be recognized as quite reliable. In particular, they are
confirmed by the letter of Khan Shikh-Akhmat to Hlynsky in 1502. The first fully authentic
representative of the clan was Prince Ivan Hlynsky (late 14th – first half of 15th centuries).
The Hlynsky principality, although very sparsely populated, occupied a vast territory along
the middle and lower flow of the Vorskla, Psel and Sula rivers. Its main centers were the towns
of Hlynsk and Poltava on the Vorskla river, as well as Hlynnitsa on the Sula.
Around 1400, the Grand Duke Vitovt granted Hlynsky possessions in Siver land, the
center of which was the town of Khorobor on the Desna river. That town existed in the place
of the modern Makoshino town, Chernigov region. «Principality» of Khorobor occupied a
strip of the territory along the river Desna about 100 km long. It consisted of, or separated
from it, the same small «principality» of Mena (Mena – the regional center of the Chernigov
region). Prince Urustay Mensky, mentioned in 1408, most likely was one of the first Hlynsky
or their close relative.